Synthesis of thinned linear antenna arrays using bees algorithm - Guney, K.; Onay, M. (Microwave and optical technology letters, 2011)
In this article, we propose a method based on the bees algorithm (BA) to synthesize thinned linear antenna arrays with low sidelobe level.The BA is an optimization algorithm inspired by the behavior of the honey bees to find the optimal way of harvesting food resources around the hive. Several examples with different thinning percentages are given to show the effectiveness of the proposed method. The results of BA are compared with the results of real coded genetic algorithm, ant colony optimization, and iterative Fourier technique. © 2011 Wiley Periodicals, Inc. Microwave Opt Technol Lett 53:795–799, 2011; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.25850